Multicentre phase II trial of trastuzumab and capecitabine in patients with HER2 overexpressing metastatic pancreatic cancer - Harder, Jan; Hofheinz, Ralf-Dieter; Büchler, Peter (British journal of cancer, 2012)
BACKGROUND: New therapeutic options for metastatic pancreatic cancer are urgently needed. In pancreatic cancer, overexpression of the epidermal growth factor receptor 2 (HER2) has been reported in up to 45%. This multicentre phase II study investigated the efficacy and toxicity of the HER2 antibody trastuzumab combined with capecitabine in the patients with pancreatic cancer and HER2 overexpression. METHODS: Primary endpoint was rogression-free survival (PFS) after 12 weeks. A total of 212 patients were screened for HER2 expression. RESULTS: Immunohistochemical (IHC) HER2 expression was: 83 (40%) grade 0, 71 (34%) grade 1, 31 (15%) grade 2, 22 (11%) grade 3. A total of 17 patients with IHC þ 3 HER2 expression or gene amplification could be assessed for the treatment response. Grade 3/4 treatment toxicities were: each 7% leucopenia, diarrhoea, nausea and hand-foot syndrome. Progression-free survival after 12 weeks was 23.5%, median overall survival (OS) 6.9 months. CONCLUSION: This study demonstrates þ 3 HER2 expression or gene amplification in 11% of patients. Contrary to breast and gastric cancer, only 7 out of 11 (64%) patients with IHC þ 3 HER2 expression showed gene amplification. Although the therapy was well tolerated, PFS and OS did not perform favourably compared with standard chemotherapy. Together, we do not recommend further evaluation of anti-HER2 treatment in patients with metastatic pancreatic cancer.